(untitled) (World of finance, 2024)
Introduction. Ensuring financial stability is one of the important aims of managing households’ financial resources. Exogenous factors constantly influence this process, the war with the russian federation is one of the most important of them. The introduction of martial law changed the regulatory rules for the functioning of the financial system, which significantly affected the process of ensuring the financial stability of households. The purpose of the article is to determine the extent to which the functioning of the financial system under martial law affects the financial stability of households. Results. The paper researches the functioning financial system under martial law and shows their positive and negative impact on ensuring the financial stability of households. The study proves the deterioration of the financial stability of internally displaced persons; the growth of income sufficiency indicators is shown only for those households that include military personnel. The analyzed trends in household incomes under martial law correlate with the dynamics of expenditures, some growth in the military government bonds. Due to the lack of full functioning of stock exchanges, the study substantiates the impossibility of realizing the investment potential of households under martial law. Conclusions. The proposed analysis shows the existence of significant limitations in ensuring the financial stability of households in wartime, namely, the inability to fully realize their investment potential and the use of certain financial instruments for savings.